2018
DOI: 10.1186/s40900-018-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

Coproduction for feasibility and pilot randomised controlled trials: learning outcomes for community partners, service users and the research team

Abstract: Plain English summaryCo-producing research with members of the public is increasingly recognised as a valuable process. Yet, despite these good intentions, the literature on coproduction has struggled to keep pace with the coproduction ‘movement’. There is a lack of clarity regarding acceptable levels of involvement and attempts at standardising approaches appear generic and lack detail. Moreover, relatively little research has captured the views of all the parties involved (academics, service providers and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 36 publications
(36 reference statements)
3
44
0
1
Order By: Relevance
“…This is consistent with research teams engaging stakeholders in other health areas such as depression and asthma. McConnell et al reported that early engagement was beneficial in that it "promoted equal ownership" [23], while Supple et al noted that engagement "is often most impactful in the project formation phase" [24]. Certainly, our own experience would support these previous observations, as we believe our early engagement of patient partners improved feasibility of incorporating their feedback, strengthened relationships, and thereby maximized impact of patient engagement.…”
Section: Benefits Of Patient Engagement In Early Phase Clinical Trialssupporting
confidence: 63%
See 1 more Smart Citation
“…This is consistent with research teams engaging stakeholders in other health areas such as depression and asthma. McConnell et al reported that early engagement was beneficial in that it "promoted equal ownership" [23], while Supple et al noted that engagement "is often most impactful in the project formation phase" [24]. Certainly, our own experience would support these previous observations, as we believe our early engagement of patient partners improved feasibility of incorporating their feedback, strengthened relationships, and thereby maximized impact of patient engagement.…”
Section: Benefits Of Patient Engagement In Early Phase Clinical Trialssupporting
confidence: 63%
“…Additionally, by working with our patient partners to develop a non-technical summary of the systematic review findings we hope to have improved the accessibility of our findings to a wider audience. A recent study similarly reported that working with stakeholder partners throughout the analysis and dissemination phases of a project not only improved the format of the article but as well allowed for incorporation of "real-world interpretations" [23].…”
Section: Benefits Of Patient Engagement In Early Phase Clinical Trialsmentioning
confidence: 99%
“…It provides a template of values and principles for working towards greater equality within research teams [ 17 ], co-producing knowledge [ 18 ]. Transitioning to research practice is not straightforward [ 19 ]. Co-production demands that researchers work differently both scientifically and practically, relinquishing and sharing established power bases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, we expect a small sample size in WP1, WP3 and WP4, due to the peculiarity of the rural and remote context that limits the generalisation of the research findings. 72 Second, the direct involvement in the design phase of the service may influence its level of innovativeness.…”
Section: Potential Limitationsmentioning
confidence: 99%